The Influence of Cynips quercusfolii on the Content of Biofunctional Plant Metabolites in Various Morphological Parts of Quercus robur - Anna Przybylska-Balcerek; Kinga Stuper-Szablewska (Molecules)
English oak (Quercus robur) hosts over 200 species of galls formed by insect larvae, most notably the oak gall wasp (Cynips quercusfolii). These galls result from the abnormal growth of plant tissue in response to oviposition, acting as a shelter and nutrient source for the larvae. In addition, the galls trigger oxidative stress in the host plant, resulting in the increased production of reactive oxygen species (ROS). This stress response promotes the biosynthesis of antioxidant compounds, including phenolic acids, flavonoids, and tannins. To our knowledge, this is the first study to monitor seasonal changes in phenolic acids, flavonoids, and tannins in relation to C. quercusfolii infestation over a complete vegetation cycle using integrated UPLC profiling and statistical modeling PCA. For the first time, the contents of phenolic acids, flavonoids, and tannins were assessed throughout the vegetation cycle—from flowering to acorn fall. Results showed that galls affect the biochemical profile of the whole plant, suggesting a systemic response to local infection. The results provide new insights into oak defense responses and suggest that gall formation may be associated with systemic metabolic shifts potentially involved in stress mitigation. Furthermore, the study supports the further investigation of oak galls as a valuable source of polyphenols for pharmacological and industrial applications.